A Note on Primary and Weakly Primary Submodules - Ulucak, Gulsen; Uregen, Rabia Nagehan (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2016)
In this paper, the generalizations of primary submodules and weakly primary submodules are proposed as P(N)-locally primary submodules and P(N)-locally weakly primary submodules, respectively. The relationships of these submodules are investigated extensively.
Keywords: Primary; Weakly primary; P(N)-locally primary; P(N)-locally weakly primary; Mathematics